(untitled) (Revista Brasileira de Iniciação Científica, 2024)
This study aimed to evaluate the water quality of Lago das Rosas, in Goiânia (GO), in the dry and rainy season of 2022. Physical-chemical and microbiological variables were analyzed, and water quality indices (IQA and IET) were calculated. The results, during the dry period, satisfied what is allowed by Conama Resolution n° 357/2005 (Class II), while in the rainy period, the variables DBO, OD and total coliforms exceeded the allowed limits, a scenario possibly due to organic pollution caused by surface water runoff. Variation that interfered in the water quality indices, which for the IQA, in the rainy period was considered “reasonable”.